Pembelajaran Kitab Arbain Nawawi untuk Internalisasi Nilai-Nilai Pendidikan Akhlak di Pondok Pesantren Roudlotul ‘Uluum Banyumas - Prayoga, Hendhi (Jurnal Kependidikan, 2024)
This article discusses learning the Book of Arbain Nawawi as a means of internalizing the values ​​of moral education at the Roudlotul 'Uluum Balong Islamic Boarding School, Banyumas. Learning the Book of Arbain Nawawi at the Islamic boarding school plays an important role in shaping the character and spirituality of the students. In this article, we will explain how studying this book is successful in internalizing moral values ​​for creatures, both towards fellow humans and towards ourselves. Apart from that, this article will also discuss the positive interactions of students with neighbors and guests as a result of implementing the moral values ​​learned at Islamic boarding schools. It is hoped that this article can provide in-depth insight into the importance of studying the Book of Arbain Nawawi in shaping the character and morality of students at the Roudlotul 'Uluum Balong Islamic Boarding School, Banyumas. Keywords Learning, Arbain Nawawi, Internalization of Values, Roudlotul 'Uluum